Electronic Hand Hygiene Quality and Duration Monitoring in Pre-School Children: A Feasibility Study - Mohd Dzulkhairi Bin Mohd Rani; Tengku Zetty Maztura Tengku Jamaluddin; Shalinawati Binti Ramli; Habibah Faroque; Farishah Nur Abd Samad; Abdul Rasyid Ariffien; Aisyah Ar Redha Che Amir Farid; Che Ilina Binti Che Isahak; Nurul Azmawati Mohamed @ Abd Aziz; Zarini Ismail (SAGE Publications Inc., 2024)
Indexed by WOS/SCOPUS